Recommended practices for laser beam welding, cutting, and allied processes (American Welding Society, 2010)
This document presents recommended practices for laser beam welding, cutting, drilling, and transformation hardening. It is intended to cover common applications of the process. Processes definitions, safe practices, general process requirements and inspection criteria are provided.
At head of title: An American national standard.
Approved by the American National Standards Institute June 24, 2010.
Supersedes ANSI/AWS C7.2:1998.
Keywords: Laser beam cutting -- Standards.; Laser beam welding -- Standards.; elektronické knihy; electronic books